The contribution of internal audit to management of the organizations: The perspective of internal auditors | [O Contributo da Auditoria Interna para a Gestão das Organizações: a Perspetiva dos Auditores Internos] - Lourenço, Pedro; Pires, Ana; Laureano, Raul M. S. (12th Iberian Conference on Information Systems and Technologies (CISTI), 2017)
In the current economic environment characterized by doubt and uncertainty the change is constant and those responsible for the organizations must be prepared to respond quickly and assertively to the challenges they face. Internal auditing activity can play a relevant role by providing information that may allow those in charge to decide with more knowledge. Hence this research evaluates the contribution of internal audit to organizations' management and identifies which organizational dynamics influence that contribution based upon a questionnaire responses from those responsible for internal audit departments of 29 large Portuguese companies. Results indicate an effective contribution of internal audit to organizations' management and identifies as enhancers of this contribution organization in internal audit, internal audit and management interaction and internal audit's team qualifications. Therefore, this research highlights the need for those responsible to ensure an alignment and articulation between management and internal audit to reflect benefits of this activity in decision-making and to gain competitive advantages.